Importancia económica de la agroindustria azucarera en el Ecuador - Demera German, Lady Julexi (2023)
This document provided pertinent information on the economic importance of the sugar industry in Ecuador. It is necessary to highlight that sugarcane is cultivated mainly for industrialized sugar production, however, it is also used as raw material for fertilizers, animal feed, paper manufacturing and distilled alcoholic beverages, thus constituting itself as a source of income generator. for Ecuadorian families, either because they are producers or in turn provide labor to carry out the tasks that the industry requires. For the detailed it was concluded that in Ecuador, the cultivation of sugar cane is cultivated in the provinces of Guayas, Imbabura, Loja and Cañar, during the months of June to December, whose raw material is the main component of the sugar industry of the country; The sugar industry is an important agricultural sector in the country, dedicated to the planting, harvesting and processing of sugar cane, generating a source of employment for people who live in sectors surrounding the industries, which improves the quality of life of many. families; The process for obtaining sugar is as follows: cutting the cane (consists of breaking or shredding the cells of the stems), later, with conveyor belts, they are led to the mills where the sucrose extraction process is carried out by generating steam, heating, clarification, filtration, evaporation, crystallization, evaporation, drying of the product and finally storage. Each of the processes must comply with quality parameters to ensure efficient operation throughout the process and current technologies allow Ecuador's sugar mills to have renewed machinery for the industrialization of the product, optimizing and continuously innovating the sugar sector to reduce production costs and that allow improving the economy, improving its profitability and productivity, which in turn generates a source of employment and economic income for Ecuadorian households.